Biomarkers response and population biological parameters in the earthworm Eisenia fetida after short term exposure to atrazine herbicide - Sofía Lammertyn (Elsevier, 2021)
Atrazine is one of the most used herbicides and its over-application in fields can affect the soils and their associated biota. In this work, earthworms (Eisenia fetida) were exposed to different concentrations of atrazine to assess possible sublethal harmful effects. In the search for reliable biomarkers of these effects, acetylcholinesterase (AChE), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) activities were measured as well as behaviour and population biological parameters such as biomass, growth and production of cocoons. It was found that biomass changes were not significantly affected by atrazine presence and after 28 days the increment was around 18.3–27.3%. Protein content in earthworms was reduced in the presence of atrazine after 28 days. The lower atrazine concentration (2 mg Kg−1) affected in the shortest term (7 days) the rate of cocoon production and increased LDH activity and, especially, the AChE activity in around 40%. The presence of a higher concentration (10 mg Kg−1) of the herbicide reduced one third of the number of total cocoons, affecting the reproduction. ALP was the least sensitive biomarker to atrazine exposure. When exposed to up to 10 mg Kg−1 of atrazine, E. fetida showed a tendency to rebalance and maintained its general health.